1999
DOI: 10.1084/jem.190.9.1329
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Receptor–Induced Activation and Cytoskeletal Rearrangement Are Impaired in Wiskott-Aldrich Syndrome Protein–Deficient Lymphocytes

Abstract: The Wiskott-Aldrich syndrome protein (WASp) has been implicated in modulation of lymphocyte activation and cytoskeletal reorganization. To address the mechanisms whereby WASp subserves such functions, we have examined WASp roles in lymphocyte development and activation using mice carrying a WAS null allele (WAS − / −). Enumeration of hemopoietic cells in these animals revealed total numbers of thymocytes, peripheral B and T lymphocytes, and platelets to be significantly diminished relative to wild-type mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
380
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(406 citation statements)
references
References 75 publications
23
380
3
Order By: Relevance
“…However, a number of recent reports have implicated these GTPases in the regulation of microtubules and cellular polarity: inhibition of Cdc42 inhibits polarization of the MTOC within a T cell hybridoma [32], Rac1 and Cdc42 transduce signals resulting in the phosphorylation and subsequent inhibition of the microtubule-destabilizing protein stathmin [33], and Cdc42 is required for integrin-induced MTOC polarization in astrocytes [34]. Such a Cdc42-dependent signal to the MTOC could be mediated by WASp, a Cdc42 effector, since WASp-deficient T cells also show defective polarization of the MTOC towards the T-cell/ APC contact site [35]. Further work is needed to establish which, if any, of these pathways may be operating during TCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent reports have implicated these GTPases in the regulation of microtubules and cellular polarity: inhibition of Cdc42 inhibits polarization of the MTOC within a T cell hybridoma [32], Rac1 and Cdc42 transduce signals resulting in the phosphorylation and subsequent inhibition of the microtubule-destabilizing protein stathmin [33], and Cdc42 is required for integrin-induced MTOC polarization in astrocytes [34]. Such a Cdc42-dependent signal to the MTOC could be mediated by WASp, a Cdc42 effector, since WASp-deficient T cells also show defective polarization of the MTOC towards the T-cell/ APC contact site [35]. Further work is needed to establish which, if any, of these pathways may be operating during TCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Haddad et al [104] demonstrated that CXCL12 induced T cell chemotaxis through Cdc42 activation and interaction with WASP. Mice with mutations in Vav or WASP exhibit deficiencies in T cell proliferation, cytoskeletal rearrangement and receptor capping [105,106]. These data indicate that cytoskeletal reorganization is important not only for T cell polarization but also for activation.…”
Section: Phosphoinositide 3-kinase (Pi3k) and Other Signaling Eventsmentioning
confidence: 93%
“…Although WASp-deficient T cells respond poorly to TCR stimulation in vitro, their proliferative responses can be partially rescued by addition of IL-2, particularly in the presence of accessory cells (6,9). To investigate whether the defective suppressor function resulted from a failure of adequate cell activation, we prestimulated CD4 + CD25 + Treg cells in the presence of anti-CD3 plus IL-2 and accessory cells for three days.…”
Section: Preactivation With Il-2 Can Partially Rescue Defects In Suppmentioning
confidence: 99%
“…The disorder is caused by mutations of WAS, the gene encoding the WAS protein, WASp, a key regulator of actin polymerization that is expressed in nonerythroid hematopoietic cells (2). T cells isolated from WASp-deficient mice and WAS patients show multiple defects including reduced TCR-induced proliferation and IL-2 production associated with impaired actin polymerization, defects which are likely to contribute to the immunodeficiency in WAS (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%